WILDMEAT interventions database: A new database of interventions addressing unsustainable wild meat hunting, consumption and trade - Willis, J.; Ingram, D.J.; Abernethy, K.; Kemalasari, D.; Muchlish,; Sampurna, Y.; Midoko Iponga, D.; Coad, L.M. (Wiley, 2022)
The urgent need to manage wild meat for the sake of both local livelihoods and wild ecosystems means that many and varied interventions have been implemented with the aim of increasing the sustainability of wild meat use. Management responsibility for these interventions can rest with different actors, from central governments (which often contract nongovernmental organisations (NGOs) to support their resource management) to private sector concessionaries (e.g. timber companies), or devolved directly to wildlife-hunting communities. Although management goals may be similar—sustainable wildlife populations and local livelihood security—the range of interventions selected, the resources invested and the expertise available differ vastly.